Sites of genocide - Jones, Adam, 1963- author.
1 online resource
Keywords: "This wide-ranging, diverse, and coherent collection of his key essays from the past decade is supplemented by previously unpublished talks, and media interviews and photographs from the author's Global Photo Archive. The book covers the global range of historical and contemporary case-studies including the Holocaust, the Long Nineteenth Century, the Bangladeshi Genocide, the Rohingya Genocide, Rwanda, the Great Lakes Genocides, Gendercide, the role of religion and the challenges of intervention. This well-structured, stimulating, and highly readable volume of his essays is suitable for undergraduate course usage and will also be of interest to Genocide scholars and interested general readers"--